Perlindungan Terhadap Hak Konsumen Atas Penarikan Paksa Kendaraan - Fauzia S. Tuna; Nur Mohamad Kasim; Suwitno Yutye Imran (Sekolah Tinggi Ilmu Administrasi (STIA) Yappi Makassar, 2023)
This study aims to determine the guarantee of the consumer protection institution foundation for consumer rights to the forced recall of vehicles. The research method used is an empirical legal research method using a descriptive approach and qualitative analysis techniques. The results of this study show that YLKI's role in guaranteeing consumer rights regarding the case of the forced withdrawal of motorized vehicles by the leasing party includes providing awareness to the public and providing advocacy and legal consultation for consumers who experience losses. On the first point In order to increase consumer awareness, LKY consistently strives to carry out community-based activities so that more and more people can find out about the materials or messages being disseminated to increase understanding and awareness of consumer rights. While providing advocacy and legal consultations for consumers who have experienced losses as an effort to fight for the rights of consumers who have suffered losses from finance companies. The two roles mentioned above are a form of guarantee of legal protection for consumers who experience losses.